Kepadatan Populasi dan Pola Distribusi Keong Mas (Pomaceae canaliculta L.) pada Ekosistem Sawah di Kecamatan Jatinangor - Vira Kusuma Dewi; Rizky Ramdhani; Tarkus Suganda; Lindung Tri Puspasari; Rika Meliansyah (Soilrens, 2022)
Golden snail (Pomacea canaliculata L.) one of a keypests in rice cultivation in Indonesia. There are three species of golden snails in Indonesia, these are P.canaliculata L., P. insularum D., and P. paludosa S. The purpose of this research was to determine the population density and distribution pattern of golden snails (P. canaliculata) at Jatinangor rice fields. The research was conducted from June 2020 to August 2020 with purposive sampling method on 24 rice fields in 12 villages, specifically Hegarmanah, Cibeusi, Cikeruh, Cipacing, Sayang, Cileles, Cilayung, Cisempur, Cintamulya, Jatimukti, Mekargalih, and Jatiroke in Jatinangor, Sumedang and golden snails identification was conducted at the laboratory. The sample was taken by using purposive sampling method. Each rice fields used as a sampling location has a size 10 m x 5 m with 2 rice fields were determined for sampling in each village. Therefore, total research location was 24 rice fields. Two lands were taken from one village with a distance of ± 1 km between the fields. This is done to get a comparison of environmental conditions. The results showed that the density of snails in the rice fields of Jatinangor was categorized rare with an average density of 3.33 individuals/m². The difference in the density of snails in each area in Jatinangor was caused by differences in the age/phase of rice plants and control techniques. Furthermore, distribution pattern of the golden snail at the rice fields of Jatinangor has a clumped pattern for all locations